PENERAPAN MODEL POE2WE YANG DI INTEGRASIKAN DENGAN BENCANA TSUNAMI SEBAGAI UPAYA PEMAHAMAN KONSEP FISIKA PADA MATERI GELOMBANG BERJALAN DAN GELOMBANG STASIONER BAGI SISWA KELAS XI SMA - Nurdiansah, Ihsan; Hujjatul Islami, Fahmi; Nana, Nana (EduFisika: Jurnal Pendidikan Fisika, 2020)
This study aims to describe the application of the POE2WE model that was integrated with the tsunami disaster on traveling wave and stationary waves. This research uses literature study method. The POE2WE model is integrated with the tsunami disaster on traveling wave material and stationary waves following the steps of prediction, observation, explanation, elaboration, write and evaluation. The POE2WE learning stages make it easier for teachers to facilitate students to learn wave material. Students can understand the concept of traveling waves and stationary waves by constructing their own knowledge which is directly related to real problems in everyday life.